2012
DOI: 10.4103/0972-2327.93270
|View full text |Cite
|
Sign up to set email alerts
|

Low cholesterol as a risk factor for primary intracerebral hemorrhage: A case-control study

Abstract: Introduction:An inverse association between serum cholesterol and the risk of hemorrhagic stroke has been noted in epidemiological studies. We performed a case–control study to assess the relationship between primary intracerebral hemorrhage (ICH) and low serum cholesterol.Materials and Methods:Prospectively recruited fully evaluated patients with ICH were compared with a control group based in a primary care practice, i.e. age- and sex-matched individuals attending the routine preventive health check-up. Low … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
16
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 21 publications
3
16
0
Order By: Relevance
“…Clinical epidemiological studies have shown that statin therapy for reducing the level of low-density lipoprotein (LDL) cholesterol was an important predictor of hematoma growth because it inhibited platelet aggregation and thrombogenesis after acute ICH. Other studies have suggested that the protective effects of statin may be due to their ability to alter endothelial function, modulate the immune system and inhibit inflammatory processes [10,[20][21][22][23][24][25]. The results of these studies have been contradictory, so we carried out a comprehensive meta-analysis of published cohort studies and found that pre-ICH statin therapy did not significantly affect post-ICH mortality, unfavorable functional outcome or hematoma volume.…”
Section: Discussionmentioning
confidence: 86%
“…Clinical epidemiological studies have shown that statin therapy for reducing the level of low-density lipoprotein (LDL) cholesterol was an important predictor of hematoma growth because it inhibited platelet aggregation and thrombogenesis after acute ICH. Other studies have suggested that the protective effects of statin may be due to their ability to alter endothelial function, modulate the immune system and inhibit inflammatory processes [10,[20][21][22][23][24][25]. The results of these studies have been contradictory, so we carried out a comprehensive meta-analysis of published cohort studies and found that pre-ICH statin therapy did not significantly affect post-ICH mortality, unfavorable functional outcome or hematoma volume.…”
Section: Discussionmentioning
confidence: 86%
“…Mean total cholesterol was also significantly low in ICH patients compared with controls (177 mg/dl vs. 200 mg/dl, p=.0006). 20 LDL-c and TG were also significantly low in ICH patients compared with controls. Although lower mean cholesterol was seen in both young and older individuals in ICH groups than in controls, the difference was significant only in older group (Age.45 years).…”
Section: Discussionmentioning
confidence: 82%
“…Low cholesterol is a known cause for intracerebral hemorrhage [15]. Cerebral microbleeds were reported in patients with hypolipidemia in association with hypertension [16]. Our patient has microbleeds without history of hypertension.…”
Section: Discussionmentioning
confidence: 85%